2018
DOI: 10.3233/bmr-169749
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stabilization exercises on diaphragm muscle thickness and movement in women with low back pain

Abstract: As a result, stabilization exercises increase diaphragm muscle thickness and improve lumbopelvic stability in women with low back pain. Therefore, stabilization exercises should be considered as a part of the treatment program in low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
4
4
0
Order By: Relevance
“…Our results show that there is an increased thickness of diaphragm during the lifting task after training which may suggest that the role of diaphragm muscle has improved in maintaining trunk stability during upper limb activities as a result of the applied 8-week-long training. Our findings are in line with a previous study of Dülger et al36 They found that as a result of a stabilization exercise program, the thickness of diaphragm increased as well as the stability of the lumbar spine 36…”
Section: Discussionsupporting
confidence: 94%
“…Our results show that there is an increased thickness of diaphragm during the lifting task after training which may suggest that the role of diaphragm muscle has improved in maintaining trunk stability during upper limb activities as a result of the applied 8-week-long training. Our findings are in line with a previous study of Dülger et al36 They found that as a result of a stabilization exercise program, the thickness of diaphragm increased as well as the stability of the lumbar spine 36…”
Section: Discussionsupporting
confidence: 94%
“…This tool evaluates pain intensity from 0 which corresponds to “no pain” to 10 which corresponds to “pain of maximum intensity”. This scale was applied for the evaluation of pain intensity in a quantitative way [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our results show that there is an increased thickness of diaphragm during the lifting task after training which may suggest that the role of diaphragm muscle has improved in maintaining trunk stability during upper limb activities as a result of the applied 8-weeklong training. Our findings are in line with a previous study of Dülger et al 83 They found that as a result of a stabilization exercise program the thickness of diaphragm increased as well as the stability of the lumbar spine. 83 Considering lumbar multifidus muscle in prone position, significant increase was only found in case of the left-sided one in the relaxed state.…”
Section: Effects Of the Conventional Exercises Completed With Diaphrasupporting
confidence: 94%
“…Our findings are in line with a previous study of Dülger et al 83 They found that as a result of a stabilization exercise program the thickness of diaphragm increased as well as the stability of the lumbar spine. 83 Considering lumbar multifidus muscle in prone position, significant increase was only found in case of the left-sided one in the relaxed state. There were no significant changes in case of contracted states of the left-sided muscle or in both states of the right- case of our testing procedure one dumbbell was lifted with both hands therefore it is possible that the dominant arm had a bigger contribution in the exercise.…”
Section: Effects Of the Conventional Exercises Completed With Diaphrasupporting
confidence: 94%